Anesthesia, Pain, Intensive Care and Emergency Medicine — A.P.I.C.E. Proceeding of the 14th Postgraduate Course in Critical Care Medicine Trieste, Italy — November 16–19, 1999 - Gullo, Antonino (Springer Milan, 2000)
The end of the second millenium is distinguished for the increasing interest in the field of critical care medicine, not only among physicians and clinical scientists but also on the part of the mass media. This is an interdisciplinary area of medicine drawing upon the specialties of anesthesiology, internal medicine and surgery, and relying upon the essential contributions and support from basic research. Advances in critical care medicine depend on the application of new technologies to the clinic, the full integration of computers and informatics, the continual training of physicians and technicians, and the consideration of ethical issues in the clinical setting. Within this complex panorama of complementary approaches and viewpoints, it is apparent that critical care medicine is one of the best examples of evidence-based medicine
Keywords: Anesthesiology; Konferenzschrift